Landscape change and fire hazard in a mountainous area in northeastern Portugal. - Moreira, César (2011)
Human abandonment in Mediterranean regions of Europe has led to vegetation encroachment and landscape homogenization reducing biodiversity and favoring the occurrence of wild fires. In Portugal, landscape changes driven by human abandonment were not observed until the late twentieth century. The full extent of these recent changes and their economic, social and ecological consequences, particularly by the creation of favorable conditions for the occurrence of large wild fires, are just partially described and understood. Additionally, research on these issues is urgently required to provide guidelines for future ecosystem and landscape planning and management. We studied land use and land cover over the last 50 years in the França Parish (Bragança, North Eastern Portugal) to evaluate change in pattern and to infer on change in function, particularly fire occurrence and propagation. We interpreted digitized and orthocorrected aerial photographs from 1958, 1968, 1980, 1993, and 2005, based on the “Carta de Ocupação do Solo” (Instituto Geográfico Português) land use/land cover system. Landscape structure for each of these dates was described based upon landscape metrics calculated for major land cover classes. Fire hazard was evaluated in terms of abundance and configuration of highly combustible cover classes. We also used the FARSITE 4 software (Finney, 1998) to simulate fire propagation at the landscape level based on land cover, terrain, and meteorological data.